Option Prices and Model-free Measurement of Implied Herd Behavior in Stock Markets - Daniël Linders; Jan Dhaene; Wim Schoutens (Tinbergen Institute, 2015)
In this paper, we introduce two classes of indices which can be used to measure the market perception concerning the degree of dependency that exists between a set of random variables, representing dierent stock prices at a xed future date. The construction of these measures is based on the theory of comonotonicity. Both types of herd behavior indices are model-free and risk-neutral, derived from available option data. Depending on its particular de nition, each index represents a particular aspect of the market sentiment concerning future co-movement of the underlying stock prices.
Keywords: G13; G14; 330; comonotonicity; herd behavior; HIX; index options; market fear; Model-free measures; VIX